Análisis de los mecanismos de compensación de multas comunitarias y su adopción en la región. caso: CC.NN. Sargento lores de camote isla, 2022 - Jaramillo Chufandama, Christian Bill (2024)
The reason for the development of this research was to analyze the process of penalty compensation mechanisms, community acceptance, and regulatory compliance in the "Sargento Lores de Camote Isla" Native Community. The objectives set out aimed to describe the formation of the community surveillance control committee, determine characteristics of the surveyed population, and identify compliance with regulations and acceptance of penalty reduction mechanisms for later comparison. This study corresponds to a cross-sectional - prospective type, with an analytical - non experimental design, whose population sample consisted of 18 community members who attended the assembly held on-site. To collect data, the survey technique and the application of the questionnaire as a validated tool according to expert judgment were used. It is reported that community acceptance for the study variables of penalty reduction mechanisms such as environmental recovery and environmental conservation through the Wilcoxon test showed no statistically significant differences given the p-value > 0.05. However, the comparison of community perception variables regarding regulatory compliance was statistically different with a p-value < 0.05, demonstrating that the community, despite being aware of the regulations, was not complying with them.